Avaliação da resistência de genótipos de grão-de-bico (Cicer arietinum L.) à Spodoptera frugiperda (Lepidoptera: Noctuidae) - Teixeira, Frederico Landim (2023)
Chickpea is one of the most cultivated legumes in the world, which brings many benefits to human nutrition and health. However, domestic production is still very low and dependent on imports from other countries. In grain cultivation, pests are responsible for impacting production numbers and generating large yield losses in cropping systems. The objective of this work was to identify sources of resistance to Spodoptera frugiperda in crop genotypes. The experiments carried out in the laboratory used the genotypes BRS Aleppo, Cicero, Flip 10 - 328C, Flip 10 - 329C, Flip 10 - 370C, Flip 10 - 379C, Flip 10 - 161C, BRS Kalifa and BRS Toro to evaluate the attractiveness in third instar caterpillars. Free-choice and freechoice tests were performed to determine the number of larvae per genotype at different time intervals, as well as to determine levels of attractiveness indexes, number of trichomes, temperature changes caused by the presence of the caterpillar, antibiosis and nutritional indices of Spodoptera frugiperda in chickpea genotypes. The results of antixenosis tests with and without choice revealed that there was no significant difference in the preference of Spodoptera frugiperda for the genotypes evaluated in the monitored time intervals. The preference indices indicated that Flip 10 - 328C was considered stimulating and Flip 10 - 370C and Flip 10 - 329C were the least attractive to caterpillar consumption in the two tests performed. Larger studies with BRS Toro, BRS Kalifa, BRS Aleppo and Flip 10 - 379C still need to be carried out so that a relationship between trichome density and levels of preference of Spodoptera frugiperda to genotypes can be better discussed, as well as for BRS Aleppo, which showed an increase in its temperature when exposed to the presence of the caterpillar. None of the genotypes considered for the antibiosis test were resistant to Spodoptera frugiperda, since they did not show results that did not show statistical difference in the larval and pupal periods, in longevity, in the total cycle and in the viability of the insect stages. The nutritional indices data revealed that BRS Toro, BRS Kalifa and Flip 10 - 329C expressed conditions so that more research on the consumption and use of these genotypes as a tool in the management of Spodoptera frugiperda could be carried out.